2004
DOI: 10.1146/annurev.earth.32.101802.120428
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Biostratigraphy—achieving Finer Resolution in Global Correlation

Abstract: ▪ Abstract  The fossil record preserves a wide range of events that might be used to build timescales and correlate strata from place to place. The events include the originations and extinctions of species, the occurrence of distinctive faunal assemblages, magnetic field reversals, changes in ocean chemistry, and volcanic ash falls. The fundamental task is to determine the global sequence of all these events. Modern computer algorithms can build high-resolution timescales by sequencing and calibrating thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 22 publications
1
73
0
2
Order By: Relevance
“…CONOP is a generalization to many dimensions of Shaw's (1964) bivariate graphic correlation approach, allowing the simultaneous comparison of event sequences from many sections. The result is a composite sequence of events for which the net misfit with all contributing sections is minimized, but no information is discarded or ignored (Sadler 2004;). An example is the graptolitebased chronostratigraphic scale for the Ordovician and Silurian (Sadler et al 2009) with its estimated tenfold improvement in resolving power over conventional zonal schemes.…”
Section: Continuity Completeness and The Geologic Time Scale (Gts)mentioning
confidence: 99%
“…CONOP is a generalization to many dimensions of Shaw's (1964) bivariate graphic correlation approach, allowing the simultaneous comparison of event sequences from many sections. The result is a composite sequence of events for which the net misfit with all contributing sections is minimized, but no information is discarded or ignored (Sadler 2004;). An example is the graptolitebased chronostratigraphic scale for the Ordovician and Silurian (Sadler et al 2009) with its estimated tenfold improvement in resolving power over conventional zonal schemes.…”
Section: Continuity Completeness and The Geologic Time Scale (Gts)mentioning
confidence: 99%
“…In addition to these direct applications, such biozonations are also of primary importance for reconstructing changes of taxonomic diversity in time and space, especially in relation with mass extinctions and recoveries (e.g., Brayard et al 2009b;Brühwiler et al 2010). To achieve these goals of accuracy and precision, a number of quantitative biochronological methods have been developed during the last decades (Hay and Southam 1978;Guex 1979;Cubitt and Reyment 1982;Gradstein et al 1985;Boulard 1993;Sadler 2004;Gradstein 2012). All these methods utilize strict and well-defined algorithms that allow not only the processing of large datasets but also to test the reliability of the underlying methods with sets of either real or simulated data of different quality.…”
Section: Quantitative Biochronological Methodsmentioning
confidence: 99%
“…In those cases, biostratigraphic correlation is more precise if it relies on the sequence of first and last appearance data of those taxa common to both areas (Blake et al, 2002;Pfefferkorn, 2003;Sadler, 2004), and eliminates taxa that have shown slow migration over time (Laveine et al, 2000;Blake et al, 2002) or regional extirpation ).…”
Section: Paleobiogeographymentioning
confidence: 99%